Zarys rozwoju zamówień publicznych w Polsce na tle państw środkowoeuropejskich: [Outline of Polish procurement law development against a background of other central Europe countries] (Studia Prawnicze / The Legal Studies, 2011)
Zamówienia publiczne to umowy cywilnoprawne, na podstawie których państwo, samorząd terytorialny lub inne instytucje prawa publicznego zapewniają na zasadzie odpłatności niezbędne do realizacji zadań publicznych świadczenia niepieniężne, zwłaszcza z zakresu budownictwa publicznego i obrotu zaopatrzeniowego. Historycznie zakorzeniona nazwa tych zamówień nie łączy się bynajmniej z powszechnym dostępem do nich, lecz ze zbiorowym przeznaczeniem kontraktowanych świadczeń, a także z potrzebą wzmożonej ochrony interesu publicznego i osłony gospodarki państwowej (komunalnej) przed rozmaitymi ułomnościami nadzoru właścicielskiego. Obecnie szczególna doniosłość zamówień publicznych wynika przede wszystkim z konieczności zagwarantowania zadowalającej efektywności wydatków ponoszonych ze środków publicznych na ich sfinansowanie Nie bez znaczenia jest też stymulacyjna rola, zwłaszcza zamówień rządowych w zakresie rozwoju konkurencyjnej gospodarki narodowej. Do tego rodzaju zamówień nie można zatem zaliczać rozmaitych świadczeń bezumownych spełnianych na rzecz państwa (samorządu) pod wpływem przymusu administracyjnego, w szczególności dawniejszych danin naturalnych i różnych świadczeń osobistych ludności, czy nawet zdarzających się jeszcze teraz rekwizycji wojennych i wywłaszczeń administracyjnych, choćby za odszkodowaniem. The evolution of procurement law in the Central Europe, starting from the ancient times, is directly a consequence of needs which arise from the necessity of preservation of, both, the sufficient effectiveness and contracting transparency in spending public funds, and further, from assurance of an equality and a competitiveness in access to works which have been funded from public funds. The evolution had been integrally connected with adequate organization, control of the treasury’s economy as well as with procedures of awarding procurement to reliable contractors, optimization of public contract’s provisions and efficient awarding party’s protection against possibility of inadequate fulfilling public contract. A construction of consensual contract underlined these procurements. Deep regress of procurement in Early Middle Ages was caused not only by the general economy recession, but mostly by disappearance of consensual contracts in aid of primitive, immediate real or formal contracts. In the area of satisfying public needs prevailing significance in the feudal part of Middle Ages had natural tributes as well as forced labour and servitude craft colonies. Revival of public procurement ensued with reactivation of trade contacts and consensual contracts, which was accompanied by transformation of state organization and also local government revival in the 10th and 11th century. Crucial impact on the development of procurements have had constitutional and political changes dated on the period of absolute monarchy, especially reforms of the Treasury. First of all organization and control of treasury expenses were improved. Also first procurements procedures for public targets have been adopted. Despite the growing importance of administrative instruments, consensual agreement maintained a leading role, primarily because of its advantages in providing satisfactory efficiency in public expenses. Development of procurement’s procedures (auction, tender) was strongly influenced by French and German models. The Polish State failed to take advantage of them because of feudal backwardness and lack of tax reforms. During the partitions of Poland, the Polish were removed not only from offices and public honors, but also from greater access to public procurement; the situation has changed only slightly in the late nineteenth century. Therefore the lack of Polish tradition in this field was noticed for a long period of time. After regaining independence in 1918, the introduction of special measures law was prevented also by problems with unification and budget. Implementation of modern procurement procedures for public purposes didn’t take place until the end of the thirties. Pre-war solutions in procurement’s procedures were formed by national practical experience and effective German and French patterns. However, World War II following by imposition of a foreign socialist system, completely blocked the development of public procurement in Poland, there was a break in legal continuity and tradition again. Meanwhile, public procurement in the countries of Western Europe experienced its further development under the influence of solutions derived from Community law. The public procurement in Poland in early nineties – as a result of the period of political changes and the reactivation of market mechanisms - was again deplorable. The situation gradually improved after passing the act on public procurement from 1994, which was amended successively given the need to implement European solutions, and then replaced (in the face of EU accession) with the new public procurement law in 2004. Next changes in Polish procurement’s procedures were a result of European law’s influence, respecting the national experience reaching pre-war domestic regulations.